American English : history, structure, and usage - Amberg, Julie S.; Vause, Deborah J. (Cambridge, UK. : Cambridge University Press, 2009)
'This lively introduction to the study of language explores American English and its place within contemporary society, highlighting the role of language in our daily lives. Beginning with a definition of language, the text unpacks the basic concepts used in linguistics, placing them in the context of real-life situations. Using examples from popular culture, the authors show how the study of language is relevant to students' experience. Teachers and students will appreciate the book's innovative structure, designed to build an understanding of how different aspects of language work together. A variety of exercises--individual, group, discussion, research--is provided to support every teaching style. Imaginatively organised and fun to use, American English is the ideal guide to language study for students taking the subject as a general education requirement, beginning undergraduates in linguistics, and future teachers of English'--Provided by publisher.
Includes bibliographical references and index.
Keywords: English language -- United States -- History; English language -- Variation -- United States; English language -- United States -- Grammar; English language -- United States -- Usage; English language -- United States -- Syntax; Americanisms